Religious diversity in post-secular societies: conceptual foundations, public governance and upcoming prospects - Sajir, Zakaria; Ruiz Andrés, Rafael (Boundaries of religious freedom: regulating religion in diverse societies, 2025)
"This book offers a multidisciplinary exploration of one of the defining characteristics of post-secular societies: religious diversity. Drawing from the sociology of religion, the sociology of migration, and related fields, it critically examines the interaction between religion, diversity, and secular governance, challenging conventional approaches to managing pluralism in contemporary contexts. Organized into three sections, the book explores: Theoretical and Conceptual Foundations: Establishing core frameworks for understanding post-secularization, pluralistic societies, and the intricate dynamics between religion and diversity. Regulating Religion in Postsecular and Diverse Societies: Analyzing policy innovation, comparative case studies, and practical challenges in managing religious diversity within secular governance structures. Navigating the Future: Prospects and Challenges of Diversity Management in Post-Secular Contexts: Addressing emerging trends such as digital transformations, the politicization of religious identities, and the evolving role of religious traditions in fostering inclusivity and resilience. Featuring contributions from leading scholars and emerging researchers, this volume provides a multidimensional perspective on debates spanning sociology, anthropology, law, and public policy. Through socio-historical examples and case studies, it examines pressing topics such as religious pluralism in secular governance, diversity management strategies, and the transformative impact of digital technologies on religious expression. At its core, the book is framed by two key concepts: post-secularization and diversity. It reexamines religion's evolving role in secularized societies, taking religious plurality--not the disappearance of religion--as a starting point for exploring secularity. This work is an essential resource for students, researchers, educators, policymakers, and professionals seeking actionable insights into critical debates on religion, migration, diversity, and secular governance in today's globalized and digitalized world" --